SILVA, Marlucilena Pinheiro da; MALUSÃ, Silvana; SANTOS, Zélia Maria de Sousa Araújo. Ensino de enfermagem: docência universitária e o princípio da integralidade do SUS. Jundiaí, Paco Editorial, 2015 / ISBN: 978-85-848-884-4 (em inglês) - Lage, Maria Isabel Gomes Sousa (Ensino em Re-Vista, 2016)
.